Cover Image, Volume 36, Issue 12. (December 2016) - Chen, Tai‐Heng; Tian, Xia; Kuo, Pao‐Lin; Pan, Hui‐Ping; Wong, Lee‐Jun C.; Jong, Yuh‐Jyh
Abstract : Prenatal ultrasonography of the third fetus at 16 gestational weeks showing multiple joint contractures (arthrogryposis). From Chen et al ., Prenat Diagn 36 : 1135‐1138, DOI:10.1002/pd.4949